Which equation illustrates the identity property of multiplication? (a bi) × c = (ac bci) (a bi) × 0 = 0 (a bi) × (c di) = (c di) × (a bi) (a bi) × 1 = (a bi)

Answers

Answer 1
Answer:

The equation that illustrates the identity property of multiplication is (a+bi) × 1 = (a+bi).

What is an equation?

An equation is formed when two equal expressions are equated together with the help of an equal sign '='.

The identity property of multiplication states that when a factor is multiplied by 1 the result is the factor itself. Therefore, the equation that illustrates the identity property of multiplication is (a+bi) × 1 = (a+bi).

Learn more about Equation:

brainly.com/question/2263981

Answer 2
Answer:

Answer:

D

Step-by-step explanation:

duh


Related Questions

The picture is the question, i need help, plz help!
PLEASE HELP, BEING TIMED, WILL GIVE BRAINLIEST!!!! Mr. Romero attached a ramp to the base of a window sill so that the family cat could more easily climb onto it. The ramp is 84 inches long. The window sill is 50 inches above the floor. What is the distance from the base of the ramp to the base of the wall?
The length and a quarter of the width of a rectangle add up to 7 in, while the length and the width add up to 10 in. What are the rectangle's length and width?
Otto used 6 cups of whole wheat flour and x cups of white flour in the recipe. What is the equation that can be used to find the value of y, the total amount of flour that Otto used in the recipe, and what are the constraints on the values of x and y?
When written in symbols, “the product ofr and s, raisedto the fourth power,” is represented as:

If the volume of a cube is 27 cubic meters, find the surface area of the cube

Answers

The formula for surface area of a cube is 6*e*e or 6e squared.

The formula for volume is e*e*e

The answer to your question would be 3 because 3*3*3 then 9*3=27 

Answer:

54square meters

Step-by-step explanation:

Volume of cube = a^3

27=a^3

a=∛27

a=3

Surface area of cube = 6a^2

Surface area=6*3^2

Surface area=6*9

surface area=54

Work out 3/4 - 1/6
Give the answer in the simplest form

Answers

(3)/(4)-(1)/(6)=(3 * 3)/(4 * 3)-(1 * 2)/(6 * 2)=(9)/(12)-(2)/(12)=(9-2)/(12)=(7)/(12)
(3)/(4)- (1)/(6) =  (3\cdot3)/(4\cdot3)  -  (1\cdot2)/(6\cdot2)  =  (9-2)/(12) [tex]= \boxed {(7)/(12) }

In the function f(x) what is f(3)

Answers

Hello there!

f(x)=x
f(x) is also known as y
x is 3, which means the x value on the right is 3

Answer: f(3)=3

X = {(2, 3), (2, 4), (2, 5), (2, 6)} is x a function and why? no, each ordered pair in this list has the same first element. yes, no two ordered pairs in this list has the same second element. yes, there is more than one ordered pair in this list. no, there is a limited number of ordered pairs in this list.

Answers

for every input, there is one output
for every x there is one y
(x,y)

if x repeats with a differnt y, it's not a function
we see
(2,3) and (2,4) and all of them

no, not a function
no, each ordered pair in this list has the same first element
answer is first one



Explain the steps necessary for solving the following equation. x^2-8x-20=0

Answers

First factor the equation
(x-10)(x+2) = 0
Then solve for (x-10) and (x+2)
x=10
x=-2
 (warning: this is quite long :P)
the steps are:

Looking at the expression x² +8x-20,we can see that the first coefficient is 1, the second coefficient is 8 and the last term is -20.
Now multiply the first coefficient (1) by the last term (-20) to get  (1)·(-20)=-20.
Now the question is: what two whole numbers multiply to -20 (the previous product).
factors of -20:
1,2,4,5,10,20
-1, -2, -4, -5, -10, -20
note: list the negative of each factor. This will allow us to find all possible combinations.
These factors pair up to multiply to -20.
1*(-20) = -20
2*(-10) = -20
4*(-5) = -20
(-1)*(20*) = -20
(-2)*(10* = -20
(-4)*(5) = -20
now let's add up each pair of factors to see if one pair adds to the middle coefficient:

first number        second number      sum

     1                           -20              1+(-20)=-19
   2                            -10              2+(-10)=-9
   4                            -5                4+(-5)= -1
 -1                            20                -1 +20= 19
 -2                              10              -2+10=8
  -4                            5                  -4+5=1

From the table above, we can see that the two numbers -2 and 10 multipy to -20 and add up to 8.
Now replace the middle term 8x with -2x+10x. Remember, -2 and 10 add up to 8. so this shows us that -2x+10x=8x.

x²+-2x+10x -20 Replace the second term 8x with -2x +10x.
(x²-2x)+(10x-20) Group the terms into two pairs.
x(x-2x)+(10x-20) Factor out the GCF x from the first group.

x(x-2)+10·(x-2) Factor out 10 from the second group. The goal of this step is to make the terms in the second parenthesis equal to the terms in the first parenthesis.

(x+10)·(x-2) Combine like terms. Or factor out thge common term x-2.
-----
ANSWER:

So, x² + 8·x -20 factors to (x+20)·(x-2.
In other words, x² + 8·x-20=(x+10)·(x-2)

THIS IS HARD TO UNDERSTAND, BUT HOPE THIS HELPED YOU! AND HOPE YOU GET IT TOO!!!
:D

Hope it helps :)


Which equation represents the vertical line passing through (7,-3)A. x=-3
B. y=-3
C. x=7
D. y=7

Answers

Answer:

B- y=-3

Step-by-step explanation: